2007
DOI: 10.1111/j.1365-2230.2007.02450.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-18 in patients with chronic ordinary urticaria: association with disease activity

Abstract: Interleukin (IL)-18 is a pleiotropic cytokine, which may play a role in autoimmune and allergic disorders. Serum IL-18 levels were measured in 34 patients with chronic ordinary urticaria (COU) and 17 normal subjects. In vivo and in vitro assays for histamine-releasing factors, an autologous serum skin test (ASST) and a basophil histamine release assay were also performed for all patients with COU. Serum IL-18 concentration was not significantly different between patients with COU and normal subjects (mean+/-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 10 publications
2
31
0
4
Order By: Relevance
“…Both studies assessed disease severity as previously described by Sabroe et al [32]. Although both studies found higher levels of serum IL-18 in patients with severe disease, these did not reach statistical significance in one of the studies [3] and were only evident in ASST-positive patients in the other [31]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies assessed disease severity as previously described by Sabroe et al [32]. Although both studies found higher levels of serum IL-18 in patients with severe disease, these did not reach statistical significance in one of the studies [3] and were only evident in ASST-positive patients in the other [31]. …”
Section: Resultsmentioning
confidence: 99%
“…Two articles [3,31] reported the relationship between interleukin 18 (IL-18) and CSU severity. IL-18 levels were measured by ELISA, with a lower limit of detection of 9.2 pg/ml [3] and by a sandwich enzyme immunoassay with a sensitivity of 12.5 pg/ml [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes that, besides the possibility of an intrinsic basophil defect, some circulating factors may favor the maintenance of activated basophils in the peripheral blood. Circulating cytokines, such as IL-18, have been suggested to be histamine-releasing factors, since IL-18 has been found at high levels in CIU patients with positive ASST in parallel with clinical severity scores [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inflammatory etiopathogenesis in CIU has been described as related to increased IL-4, IL-13, and IL-18 serum levels [13][14][15]. Cytokines in the circulation are a feature of amplified inflammation in chronic urticaria that may be helpful in understanding the immunopathogenesis of the idiopathic variety of chronic urticaria.…”
Section: Introductionmentioning
confidence: 97%